Immunological Basis of the Endometriosis: The Complement System as a Potential Therapeutic Target - Agostinis, Chiara; Balduit, Andrea; Mangogna, Alessandro; Zito, Gabriella; Romano, Federico; Ricci, Giuseppe; Kishore, Uday; Bulla, Roberta (Frontiers in Immunology, 2021)
Endometriosis (EM) is a chronic disease characterized by the presence and proliferation of functional endometrial glands and stroma outside the uterine cavity. Ovaries and pelvic peritoneum are the most common locations for endometrial ectopic tissue, followed by deep infiltrating EM sites. The cyclic and recurrent bleeding, the progressive fibrosis and the peritoneal adhesions of ectopic endometrial glands, may cause different symptoms depending on the origin involved. EM is a frequent clinical condition affecting around 10-20% of women of mainly reproductive age, as well as post-menopausal women and adolescents, especially with uterine anomalies. The risk of developing EM depends on a complex interaction between genetic, immunological, hormonal, and environmental factors. It is largely considered to arise due to a dysfunction of immunological surveillance. In fact, women with EM exhibit altered functions of peritoneal macrophages, lymphocytes and natural killer cells, as well as levels of inflammatory mediators and growth factors in the peritoneal fluid. In EM patients, peritoneal macrophages are preponderant and highly active compared to healthy women. Peritoneal macrophages are able to regulate the events that determine the production of cytokines, prostaglandins, growth factors and complement factors. Several studies have shown alteration in the regulation of the complement activation, leading to chronic inflammation characterized in EM. Aberrant regulation/activation of the classical and lectin pathways of the complement system has been observed in the peritoneal cavity of women affected by EM. Thus, complement inhibition may represent a new approach for the treatment of EM, given that a number of complement inhibitors are under pre-clinical and clinical development. Such an intervention may provide a broader therapeutic control of complement-mediated inflammatory damage in EM patients. This review will focus on our current understanding of the role of complement activation in EM and possible modalities available for complement-based therapy in the clinical practice.